2002
DOI: 10.1021/es011262j
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Particle Transport Events Controlling PAH and PCB Cycling in Grand Traverse Bay, Lake Michigan

Abstract: To evaluate the influence of episodic events on particle and hydrophobic organic contaminant (HOC) cycling in the Great Lakes, we deployed sequencing sediment traps at two locations in the western arm of Grand Traverse Bay, Lake Michigan. The traps collected integrated samples of settling particles every 2 weeks from May 1997 to September 1999. The total polycyclic aromatic hydrocarbon (t-PAH) and total polychlorinated biphenyl (t-PCB) settling fluxes from the surface waters in the southern site were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
(59 reference statements)
2
11
0
Order By: Relevance
“…The arithmetic average flux of PCBs was 0.63 ± 0.34 ng m −2 d −1 , while the corresponding time‐weighted average flux approached 0.45 ng m −2 d −1 . Overall, the ΣPCB fluxes observed in our study are 1 to 3 orders of magnitude lower than those found in the southwestern Mediterranean [ Dachs et al , 1996], the northern Baltic Sea [ Strandberg et al , 1998], the Great Lakes [ Jeremiason et al , 1998; Baker et al , 1991; Schneider et al , 2002], the Chesapeake Bay [ Ko et al , 2003], the southern Swedish lakes [ Larsson et al , 1998] and a rural U.K. lake [ Sanders et al , 1996] (Table 2). This discrepancy can be explained by the limited consumption and emissions of PCBs in countries of the eastern Mediterranean Sea [ Breivik et al , 2002b] and by the especially low settling fluxes of particulate matter at the same region (Figure 2a).…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…The arithmetic average flux of PCBs was 0.63 ± 0.34 ng m −2 d −1 , while the corresponding time‐weighted average flux approached 0.45 ng m −2 d −1 . Overall, the ΣPCB fluxes observed in our study are 1 to 3 orders of magnitude lower than those found in the southwestern Mediterranean [ Dachs et al , 1996], the northern Baltic Sea [ Strandberg et al , 1998], the Great Lakes [ Jeremiason et al , 1998; Baker et al , 1991; Schneider et al , 2002], the Chesapeake Bay [ Ko et al , 2003], the southern Swedish lakes [ Larsson et al , 1998] and a rural U.K. lake [ Sanders et al , 1996] (Table 2). This discrepancy can be explained by the limited consumption and emissions of PCBs in countries of the eastern Mediterranean Sea [ Breivik et al , 2002b] and by the especially low settling fluxes of particulate matter at the same region (Figure 2a).…”
Section: Resultsmentioning
confidence: 49%
“…The Mediterranean Sea, and especially the eastern basin, has always been considered to be one of the most oligotrophic regions in the world with a characteristic overall nutrient deficit [ Ignatiades , 1969]. Overall, the mass fluxes measured in our study were similar with those previously observed in southern Ionian Sea (0.28 to 446 mg m −2 d −1 [ Rutten et al , 2000]) and southern Cretan Sea (3.3 to 459 mg m −2 d −1 [ Stavrakakis et al , 2000]) but considerably lower than those reported for southern Swedish lakes (380 to 1.2 × 10 4 mg m −2 d −1 [ Larsson et al , 1998]), Lake Michigan (40 to 5500 mg m −2 d −1 [ Schneider et al , 2002]) and for the Chesapeake bay (1500 to 3.8 × 10 5 mg m −2 d −1 [ Ko et al , 2003]).…”
Section: Resultsmentioning
confidence: 97%
“…For example, the input of particulate matter and associated isotopes from the Yangtze plume has significant effects on 210 Po residence times in surface water in the East China and Yellow Seas [ Nozaki et al , 1991]. A few studies [ Baker and Eisenreich , 1989; Baker et al , 1991; Jeremiason et al , 1998; Schneider et al , 2002] have assessed the material input from bottom sediments (such as PCBs and PAHs) through mechanisms other than dispersion/diffusion such as particle resuspension. This process is particularly important in nearshore regions.…”
Section: Introductionmentioning
confidence: 99%
“…(2) PAHs also tend to associate with fine grained particles (Birch and Taylor, 2000;Schneider et al, 2002;Talley et al, 2002), in which TOC may be greatly enriched. However, high current velocity in the Old Yellow River Estuary may deter the deposition of fine suspended particles and thus cause low PAH concentration here (Chen et al, 2006).…”
Section: Pah Contamination In Surface Sedimentsmentioning
confidence: 99%